Repeated-Doses Toxicity Study of the Essential Oil of Hyptis martiusii Benth. (Lamiaceae) in Swiss Mice. (10th September 2013) - Freire Rocha Caldas, Germana; Araújo, Alice Valença; Albuquerque, Giwellington Silva; Silva-Neto, Jacinto da Costa; Costa-Silva, João Henrique; de Menezes, Irwin Rose Alencar; Leite, Ana Cristina Lima; da Costa, José Galberto Martins; Wanderley, Almir Gonçalves
Abstract : Hyptis martiusii Benth. (Lamiaceae) is found in abundance in Northeastern Brazil where it is used in traditional medicine to treat gastric disorders. Since there are no studies reporting the toxicity and safety profile of this species, we investigated repeated-doses toxicity of the essential oil of Hyptis martiusii (EOHM). Swiss mice of both sexes were orally treated with EOHM (100 and 500 mg/kg) for 30 days, and biochemical, hematological, and morphological parameters were determined. No toxicity signs or deaths were recorded during the treatment with EOHM. The body weight gain was not affected, but there was an occasional variation in water and food consumption among mice of both sexes treated with both doses. The hematological and biochemical profiles did not show significant differences except for a decrease in the MCV and an increase in albumin, but these variations are within the limits described for the species. The microscopic analysis showed changes in liver, kidneys, lungs, and spleen; however, these changes do not have clinical relevance since they varied among the groups, including the control group. The results indicate that the treatment of repeated-doses with the essential oil of Hyptis martiusii showed low toxicity in mice.